MANAJEMEN PEMBELAJARAN DALAM IMPLEMENTASI KURIKULUM 2013 YANG BERKARAKTER PADA SISWA SMK 3 BANDA ACEH - Marlina .; Yusrizal .; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
Learning management is a management related to planning, implementing, and evaluating learning outcomes. The objective of this research was to identify the learning management in implementing 2013 curriculum and character building of students at Vocational School (SMK) 3 of Banda Aceh. This qualitative research was conducted by means of observation, interview, and documentation as the instruments in the process of data collection. The principal, the head of instructional division, the head of culinary art program, teachers, students, and supervisors were the subjects of this research. The data collected were then analyzed by using Miles and Huberman’s methods which cover data reduction, data display, and verification. The results indicated that teachers’ (1) planning included annual program, semester program, weekly program, effective hours, and lesson plans. (3) In addition, the implementation of teaching and learning process was not in accordance with the lesson plans and scientific approach was not maximally implemented. Learning models and teaching methods chosen were not reallly appropriate. (3) Evaluation was done in each teaching and learning process, in the middle of semester, and at the end of the semester. Keywords: learning management, implementation of 2013 curriculum